Influence of Squalene on Cholesterol Levels in Albino Rats - Mathew, Susheela; K., Ammu; K., Devadasan (Fishery Technology, 2025)
Addition of 2% squalene to diets of albino rats was not found to decrease the total cholesterol levels in their serum, heart or liver. It resulted in an increase in cholesterol levels in serum, heart and liver. No beneficial effect was seen in HDL cholesterol levels also. Squalene seems to have no effect on the relative sizes of heart and liver and also on the weight gain of rats. Significance of these findings is discussed.